Pengaruh Sinergi Manajemen Gereja dan Kepemimpinan Transformasional terhadap Efektivitas Multiplikasi Pemimpin dalam Ekosistem Digital - Melki Solon; Yap Hok Gi; Anderson Daniel Sudarto (Pusat Riset dan Inovasi Nasional, 2026)
Entering the third decade of the 21st century, the church faces the urgency of redefining its existence amidst the shift to a digital ecosystem. This research aims to analyze the synergy between church management and transformational leadership toward the effectiveness of leader multiplication in the Digital 4.0 era. Using a qualitative method with a descriptive-analytical approach through library research, this study explores the integration of modern management theories and theological principles. The findings indicate that church management serves as a vital infrastructure providing operational stability, while transformational leadership acts as a catalyst for innovation and behavioral change in facing VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) conditions. The synergy between these two elements creates a “Digital Shepherding” model, where the digital space is transformed into a theological medium for character formation and spiritual transmission. The study concludes that the effectiveness of leader multiplication is determined by a shift from person-centered leadership to a system-inspired approach that integrates digital capabilities with biblical integrity. Strategic implications suggest that churches must adopt a digital mindset and establish digital leadership laboratories to ensure the sustainability of their mission among Generation Z.